Caracterização química e biológica de feromônios de Amblyomma cajennense (Fabricius, 1787) (Acari: Ixodidae) - GACHOKA, Kennedy Kiriira (2010)
Amblyomma cajennense, commonly known as Cayenne tick, is a three-host tick widely distributed in Brazil and in the rest of Latin American countries. Owing to its low host specificity, it plays an important role in the transmission of pathogens in animals and man. Chemical communication is a vital component in tick biology whereby pheromones are largely responsible in the regulation of mating, recognition of sexual partner and copulation. By understanding the behaviour of A. cajennense and the pheromones involved, there exists practical possibility for the use of these substances as an additional method of control thereby reducing the use of acaricides. Based on this, the aims of this work were to quantify and elucidate behaviours induced by pheromones emitted by females A. cajennense as well as identify and characterize qualitatively and biologically the pheromone produced by males. Engorged females were collected from naturally-infested horses for the establishment of laboratory colonies for use in this study. The pheromones were obtained by extraction in hexane and sonication by ultra-sound of fed males and females. The female sex pheromone, 2,6-dichlorophenol (2,6-DCP), was quantified by GC/MS using internal standard and standard addition methods through construction of calibration curves using 5-bromine-4-hydroxy-3-methoxybenzaldehyde and 2,6-DCP, respectively. The male extract was analysed chemically by GC/MS in comparison with standards. As concerns biological tests, glass beads were treated with two femaleequivalents of the female pheromone and 2,6-DCP in an equivalent concentration and exposed to males to observe the induced behaviour(s). Attraction to the male pheromone was evaluated by release of individual unfed, virgin females to three concentrations (1, 5 and 10 male-equivalents) of the extract in olfactometer bioassays. Orientations towards the odour source were analysed by Kruskal-Wallis and displacement angles by Circular Statistics. Aggregation was evaluated by releasing the tick stages in Petri dish bioassays shortly followed by introduction of filter paper strips impregnated with 10 male-equivalents of the extract and recording tick responses on camera. Data analysis was by Chi-square test. Tests for attachment were carried out in vivo in rabbits, Oryctolagus cuniculus, and the released ticks observed in determined intervals between 20min and 24hrs. The data was analysed by Wilcoxon signed-ranked test and Friedman s repeated measures ANOVA. The results indicated that each female emits 2.15 ng ml-1 of pheromone on average. The male extract was positive for benzoic acid, nonanoic acid, salicylic acid, benzaldehyde, 2,6-DCP, limonene and methyl salicylate. The female extract and 2,6- DCP stimulated mounting in up to 80% and 73% of all cases, respectively, confirming that 2,6-DCP alone mediates mounting behaviour in A. cajennense. There was no statistically significant attraction or aggregation in males or females induced by the male pheromone. However, significantly faster and greater attachment was recorded in both. The behavioural responses corresponded with the pheromone s composition. It was concluded that the male pheromone promotes neither attraction nor aggregation but is responsible for faster fixation of A. cajennense adults. The pheromone also contains different proportions and differs from other Amblyomma species as far as the presence or absence of certain components is concerned. The results serve as a first step in advanced studies aimed at development of novel strategies for the management of this species using these pheromones.